The Influence of Time Budget Pressure and Audit Risk on Audit Quality at Public Accounting Firms in Medan - Piter, Jhon; Ismayuni, Tri Utari; Sipahutar, Tetty Tiurma Uli (Cattleya Darmaya Fortuna, 2025)
This research aims to analyze the influence of time budget pressure and audit risk on audit quality at public accounting firms in Medan. Time budget pressure is a situation where auditors must allocate resources effectively. Audit risk is a measure of the reliability of the information used by the accounting system, namely the amount of confidence that can be given to that information. Assessment of audit quality can be based on the accuracy of the information reported by the auditor regarding whether his findings are good or not regarding the existence of a violation that occurred in the accounting system. This research was carried out at the Public Accounting Firm in Medan City using quantitative research with several methods, namely questionnaires and interviews. The population used was 50 auditors and the sample size used was 30 auditors. The research results show that audit quality can be explained by 89.9% and the remaining 10.1% is explained by factors not examined in this research. The results of this research provide important insight into the fact that high-time budget pressure and audit risk will also cause auditors to make errors when presenting material or financial reports.